(untitled) (Asian Journal of Social Science Studies, 2022)
Tess of the d’Urbervilles is written by Thomas Hardy, first published serially in 1891. The subtitle of this novel is called A Pure Woman Faithfully Presented as Hardy believes the heroine is a virtuous victim of a rigid Victorian moral code. In this novel, Hardy engages the imagery of sun with the action and the theme by different artistic skills. As a novelist with keen insight, Hardy sees natural surroundings among the important formative influences of a person’s life, especially for Tess. Hardy makes frequent use of this instinctive response to climate and geography. The novel is structured so that events take place in seasons which are artistically appropriate. At the most beautiful, productive season of the year, Nature appears to be striving for perfection: everything tends towards wholeness. Yet in the bleak and cold seasons one must go through all the difficulties and disillusionment. The symbol of the sun and the alternation of the seasons give this novel its everlasting complexity and tension.